IMPLEMENTATION OF EXCELLENCE SERVICE TO INTERNAL CUSTOMERS IN THE SERVICES OF SCHOOL ADMINISTRATION PERSONNEL AT SMP QURANPRENEUR INDONESIA PALEMBANG CITY - Oktarina, Wulan; Zainuri, Ahmad; Nurlaila, Nurlaila; Annur, Saipul (Conciencia, 2024)
This research uses a qualitative method with the type of case study approach with research informants namely principals, school administrators, teaching staff, and students. The data collection techniques used were observation, interview, and documentation and analysed using qualitative data analysis techniques. The results of this study are the implementation of excellence service to internal customers in school administration services at Smp Quranpreneur Indonesia Palembang City needs to be improved again from the aspect of actions taken by school administration personnel in the implementation of excellence service is somewhat less responsive in responding, the level of communication of school administration personnel with students who are still lacking, as well as the unavailability of SOPs (Standard Operating Procedures) for school administration personnel in carrying out their duties. Then for the supporting factors for the implementation of excellence service to internal customers in school administration services at Smp Quranpreneur Indonesia Palembang City, namely the awareness of administrative staff to provide excellent service, the existence of qualified human resources, and the direction and motivation provided. While the inhibiting factors, the school has not provided training or socialisation to improve the implementation of excellence service in administrative services to improve capabilities, there is no facility in the form of a suggestion and criticism box, and there is no SOP (standard operating procedure) to support the implementation of excellence service in administrative services.